Biallelic ANKS6 mutations cause late-onset ciliopathy with chronic kidney disease through YAP dysregulation - Schwarz, Hannah; Popp, Bernt; Airik, Rannar; Torabi Sarijalo, Nasrin; Knaup, Karl; Stoeckert, Johanna; Wiech, Thorsten; Amann, Kerstin Ute; Wiesmann da Silva Reis, André; Schiffer, Mario; Schueler, Markus; Wiesener, Michael (Human Molecular Genetics, 2022)
Nephronophthisis-related ciliopathies (NPHP-RC) comprises a group of inherited kidney diseases, caused by mutations in genes encoding proteins localizing to primary cilia. NPHP-RC represents one of the most frequent monogenic causes of renal failure within the first three decades of life, but its molecular disease mechanisms remain unclear. Here, we identified biallelic ANKS6 mutations in two affected siblings with late-onset chronic kidney disease by whole-exome sequencing. We employed patient-derived fibroblasts generating an in vitro model to study the precise biological impact of distinct human ANKS6 mutations, completed by immunohistochemistry studies on renal biopsy samples. Functional studies using patient-derived cells showed an impaired integrity of the ciliary inversin compartment with reduced cilia length. Further analyses demonstrated that ANKS6 deficiency leads to a dysregulation of Hippo-signaling through nuclear yes-associated protein (YAP) imbalance and disrupted ciliary localization of YAP. In addition, an altered transcriptional activity of canonical Wnt target genes and altered expression of non-phosphorylated (active) beta-catenin and phosphorylated glycogen synthase kinase 3 beta were observed. Upon ciliation, ANKS6 deficiency revealed a deranged subcellular localization and expression of components of the endocytic recycling compartment. Our results demonstrate that ANKS6 plays a key role in regulating the Hippo pathway, and ANKS6 deficiency is linked to dysregulation of signaling pathways. Our study provides molecular clues in understanding pathophysiological mechanisms of NPHP-RC and may offer new therapeutic targets.
CRIS-Team WoS Importer:2022-05-13

PI(3,4)P2-mediated cytokinetic abscission prevents early senescence and cataract formation - Gulluni, Federico; Prever, Lorenzo; Li, Huayi; Krafcikova, Petra; Corrado, Ilaria; Lo, Wen-Ting; Margaria, Jean Piero; Chen, Anlu; De Santis, Maria Chiara; Cnudde, Sophie J.; Fogerty, Joseph; Yuan, Alex; et al. (Science, 2021)
Cytokinetic membrane abscission is a spatially and temporally regulated process that requires ESCRT (endosomal sorting complexes required for transport)–dependent control of membrane remodeling at the midbody, a subcellular organelle that defines the cleavage site. Alteration of ESCRT function can lead to cataract, but the underlying mechanism and its relation to cytokinesis are unclear. We found a lens-specific cytokinetic process that required PI3K-C2a (phosphatidylinositol-4-phosphate 3-kinase catalytic subunit type 2a), its lipid product PI(3,4)P2 (phosphatidylinositol 3,4-bisphosphate), and the PI(3,4)P2–binding ESCRT-II subunit VPS36 (vacuolar protein-sorting-associated protein 36). Loss of each of these components led to impaired cytokinesis, triggering premature senescence in the lens of fish, mice, and humans. Thus, an evolutionarily conserved pathway underlies the cell type–specific control of cytokinesis that helps to prevent early onset cataract by protecting from senescence.
CRIS-Team Scopus Importer:2021-12-24